Evaluation of serum procalcitonin as a significant marker in cases of septic arthritis and osteomyelitis: a two year study - Koramutla, Harsha Kumar; Koyagura, Balakondaiah; Ravindran, Bijju (International Journal of Research in Orthopaedics, 2018)
Background: Acute bone infections like septic arthritis and osteomyelitis are a serious threat in management and diagnosis in the department of orthopaedics. Biochemical marker is needed with good sensitivity and specificity in diagnosing acute bone and joint infections. The aim of the present study was to study the role of PCT in conditions of septic arthritis and osteomyelitis. Methods: A two year prospective study was done and cases were grouped into three group and laboratory parameters TC, ESR, CRP and PCT were measured. The sensitivity, specificity and predictive values were compared using SPSS software version 20. Results: 238 patients, (males- 154 & Females– 84) with mean age 34.1±8.20 years. Group-1 included 52 patients with raised PCT and MRSA and Klebsiella as the common isolates. Group-2 with 89 patients and mean PCT in the study group was 4.99 ng/ml. Ninety seven were included in Group-3. The mean PCT value was 2.6 ng/ml. In group-1, the specificity of PCT (comparing Group-1 & 3) was 96.8 [95% CI, 94.2 -98.4], the sensitivity (26% [3.2-60.1], the PPV 16.1% [95% CI 2.3-48.3] and the NPV was 98% [95% CI, 95.5-99.8]. Conclusions: To conclude our study, highlights the role of PCT as a sensitive and specific marker in diagnosing cases of septic arthritis and Osteomyelitis. This opens a gateway to further research in evaluating the PCT effectiveness as a response marker to treatment. PCT is more sensitive than CRP in acute bone and joint bacterial infections and raises early and faster.